Self-Updating Approach for Filippov-Type Discontinuous Dynamical Models with Time-Varying Parameters - Huang, Jianzhe; Xiao, Binghang (Discontinuity, Nonlinearity, and Complexity, 2026)
The dynamical model for a dynamical system might change during its full life cycle, and it is important to update the corresponding model during such a system is on duty. In this paper, a Filippov-type discontinuous dynamical system which is consisted with multiple sub-systems is investigated. The switching functions for such a discontinuous dynamical system switching from one sub-system to another, as well as the system parameters of the sub-systems are considered to be time-varying. When such a Filippov-type discontinuous dynamical system is governed by one of the sub-systems, the actual excitations including internal and external forces will be evaluated through super-twisting sliding mode observer and recursive least squares in case of inaccurate sub-system modeling and system parameters variation. The event-triggered technique will be adopted to identify the change of the switching functions, and a novel method to updating the switching functions will be designed. The generalized equations of such a self-updating approach will be provided for such a Filippov-type discontinuous dynamical model, which can be further extended to build the confidential digital twin model.